A double four-point probe method for reliable measurement of energy conversion efficiency of thermoelectric materials. (15th January 2020) - Zhu, Qing; Ren, Zhifeng
Abstract: A thermoelectric material's efficiency in converting heat to electricity is its most important factor for considering the material for practical applications. Therefore, accurately measuring the conversion efficiency of any thermoelectric material is essential. However, the electrical contact layers without resistance between a thermoelectric material and electrodes, which are very difficult if not impossible to make, are required to reliably demonstrate the actual conversion efficiency. Here we report a double four-point probe method that can reliably measure the conversion efficiency of any thermoelectric material without the need to make the contact layers. In this method, copper foils acting as electrodes are mechanically pressed on the ends of the thermoelectric leg to conduct the measurement. Conversion efficiency for Mg3 Sb2 -based thermoelectric materials was measured to be ∼12.4% at a temperature difference of ∼420 °C, consistent with the predicted value from COMSOL Multiphysics, a finite element-analysis tool that reliably predicts the measured efficiencies. This method can be applied to any thermoelectric material without undertaking the tedious contact-fabrication process, which is important for rapidly screening thermoelectric materials, although practical applications still require reliable contacts. Highlights: A new method to measure the efficiency of thermoelectric materials was developed. An ultrahigh conversion efficiency of 12.4% was measured. COMSOL Multiphysics was applied to verify the measurements. Uncertainties in the measurements were eliminated by all available means.